(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
The physicochemical parameters comprise pH, temperature (T), chemical oxygen demand (COD), alkalinity, and ammonia NH3, . The results obtained in this study were as follows: temperature (21.6 -23.7ºC), pH (7.69 - 7.51), ammonia NH3 is in range 0 to 1.8 mg/L and Chemical oxygen demand (COD) is in range ( 13 – 620mg/L), and alkalinity (370-200 mg/L). . We conclude that these municipal sewage plants are important point sources of pollution in surface water with possible public health and ecological risks. The present paper comprises of the various Physico-Chemical parameters and technologies used in waste-water treatment, with emphasis on municipal waste-water.